Effectiveness of Using Canva-Based Learning Media on Physics Education - Siti Hajar; Silvia Anggri Wijaya; Umi Purnama; Hutry Handayani Isra; Mawardi Jalil Masri; Adeline Silaban (Postgraduate, University of Mataram, 2026)
This study aims to find out how effective learning is using Canva application-based learning media. This research is a research and development (R&D). Actually, there are ten stages of development, but in this study, the researcher only limited three stages in the development of Canva media, namely the planning stage, the development stage, and the trial stage. The test subjects in this study are students of Physics Education at Cenderawasih University. The data collection technique used in this study is in the form of a questionnaire or questionnaire in the form of a checklist. The data collected is in the form of quantitative data and qualitative data that is formed by words. The data analysis technique used in this study is descriptive. Based on the data analysis that has been carried out, students have responded well to the use of the Canva application. In this study, the researcher used 2 indicators in general, namely the effectiveness of learning and the learning process. The results of the analysis obtained were the percentage score for learning effectiveness of 79.46% in the good category, while for the presentation learning process obtained was 80.71 and in the good category. From the results of the analysis mentioned above, it can be said that the use of Canva-based learning media is good or effective in learning physics at Cenderawasih University.